House with sukkah – sign of Jewish heritage. Protection Issues - Michalska-Nakonieczna, Małgorzata (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
The varied cultural landscape of Polish cities and towns abounds in often unnoticed examples of former coexistence of cultures and religions. The Jewish sukkah, inside which the followers of Judaism would spend 7 days during the autumn holiday of Sukoth, is such a mark that still exists today near many residential buildings. In Poland, due to the climate and culture, the sukkah took the form of wooden or brick structures, walled-off balconies, loggias or verandas, which all featured an opening roof. The hatch was often operated with complex mechanical devices - products of folk engineering and ingenuity. Quite often the shed’s outside was richly decorated. The current state of surviving sukkah, which make a vital element of the cultural landscape of Polish towns, is usually very bad. The knowledge about the sukkah, as an element of Polish cultural heritage, should be promoted and currently existing interest should be exploited. It is vital to initiate the creation of academic and historical studies, strengthen legal protection and teach local authorities, owners and property managers.